ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT DALAM PENGAMBILAN KEPUTUSAN MANAJEMEN PADA PT. BPR PRISMA DANA MANADO - Simangunsong, Natalina Tiur Angel; Ilat, Ventje; Elim, Inggriani (Universitas Sam Ratulangi, 2018)
The statements of cash flows report cash flows over a specified period and are classified according to operating, investing and financing activities. The creation of a cash flow statement, enables each company to predict its progress so that company does not experience any losses. This research determines whether the preparation of cash flow statement from PT. BPR Prisma Dana Manado is based on PSAK Number 2, 2015 and to also determine whether its cash flow is used as the basis for management decision making. This research is a qualitative research. The results of this research in PT. BPR Prisma Dana Manado shows that in the preparation of its cash flow statement, the company uses PSAK Number 2, 2015 as its guidelines using indirect method. In its management decision making, PT. BPR Prisma Dana Manado uses analysis of cash flow statement as the basis to determine its policies.Keywords: Analysis, Cash Flow Statement, Management Decisions